A study on the damage of fire resistance material of steel structure / Farah Nadiah Mohamad Fauzi - Mohamad Fauzi, Farah Nadiah (Faculty of Architecture, Planning and Surveying, 2013)
This dissertation is conducted in order to study on the damage of fire resistance material o f steel structure. It includes the investigation on the types o f fire resistance that are commonly applied on steel structure, indentify the main causes o f fire resistance damage on steel structure and also to recommend the best practice to ensure that the fire resistance can function properly as insulation o f fire for steel structure. The data that have been collected in this dissertation is obtained through the observation on selected case studies which is selected based on the type of structure used, maintenance approach, types of fire resistance system used and the types of fire resistance damage in the steel structure building. Thus, all the information was collected through an interview and questionnaire that carried out with the relevant parties and persons who implement the fire resistance in the construction industry. Based on the analysis, it can be concluded that there are many types of fire resistance material used in the construction industry such as boarding and casing, intumescent and cementitious. Each type of fire resistance material offers a different combination of physical and chemical properties, and each has its own application requirements. Unfortunately, by poorly designed, installed, and/or maintained fire resistance will not likely provide the expected level of protection during a fire. In order to achieve the expected level or standard of fire resistance, all parties in the construction team especially the main contractors should play their roles to responsible for ensuring the material is properly procured and installed, and is inspected and recorded by all interested parties in order to make the fire resistance can be function properly as material that insulate steel structures from the effects o f the high temperatures that may be generated in fire.